2011
DOI: 10.2308/accr.00000045
|View full text |Cite
|
Sign up to set email alerts
|

Principles-Based versus Rules-Based Accounting Standards: The Influence of Standard Precision and Audit Committee Strength on Financial Reporting Decisions

Abstract: Recent accounting scandals have resulted in regulatory initiatives designed to strengthen audit committee oversight of corporate financial reporting and have led to a concern that U.S. GAAP has become too rules-based. We examine issues related to these initiatives using two experiments. CFOs in our experiments exhibit more agreement and are less likely to report aggressively under a less precise (more principles-based) standard than under a more precise (more rules-based) standard. Our results also indicate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
174
0
19

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 247 publications
(200 citation statements)
references
References 31 publications
7
174
0
19
Order By: Relevance
“…In the model adjusted by stepwise, the years 2011 and 2012 had a significantly higher average comparability when compared to 2004. The results found corroborate other researches addressing the quality of accounting information (Collins, Pasewark, & Riley, 2012;Psaros & Trotman, 2004;Agoglia, Doupnik, & Tsakumis, 2011) and prove the superiority of the principle-based standard also over the comparability of financial reports. The main conclusion of this research is that increasing manager's discretionary power through flexibility of accounting standards does not decrease the comparability of financial reports.…”
supporting
confidence: 80%
See 4 more Smart Citations
“…In the model adjusted by stepwise, the years 2011 and 2012 had a significantly higher average comparability when compared to 2004. The results found corroborate other researches addressing the quality of accounting information (Collins, Pasewark, & Riley, 2012;Psaros & Trotman, 2004;Agoglia, Doupnik, & Tsakumis, 2011) and prove the superiority of the principle-based standard also over the comparability of financial reports. The main conclusion of this research is that increasing manager's discretionary power through flexibility of accounting standards does not decrease the comparability of financial reports.…”
supporting
confidence: 80%
“…According to the authors, their findings contradict the arguments that inaccurate standards taking into account the substance under the form makes them less effective to fight biases in financial reports when compared to rule-based standards. Corroborating the findings of Psaros and Trotman (2004), Agoglia et al (2011) observed in their experiments that financial directors subject to a more flexible regulatory system are less exposed to aggressive practices in financial reporting than financial directors in stricter systems. Overall, based on these studies, we notice the existence of a proven superiority of the standard based on principles over the standard based on rules.…”
Section: Figurementioning
confidence: 60%
See 3 more Smart Citations